O trabalho docente colaborativo na perspectiva da educação inclusiva - (:unkn) unknown (Universidade Federal do Pampa, 2019)
In the present scenery of the special education we can say that the Specialized Educational Attendance (AEE), the shared performance among the specialized teachers of common classes and the planning of accessible class are the relevant elements in the context of the education in the inclusive perspective (BRASIL, 2008; 2011; 2015). With the intentionality to collaborate with the classes planning organization and systematize the teaching practice in the referring educational paradigm , in the intention to create exchanges and strategies planning that come to regard the several ways of the students learning, this dissertation presents the results of an action- research which objective was to discuss and to implement the process of inclusive teaching-learning, throughout the collaborative teaching work, with the focus in the pedagogical accessibility. The implementation of the research ocurred in the four phases of the process of the action-research (DIONNE, 2007) in which took place the aplication and compilation of the collected data during the research. For the data collection were used different instruments, among them: semi-structered questionaire, research diary, formation circles and pedagogical workshops. The evaluation instruments of the production data workshops were organized and analyzed based on the analysis categories according to (BARDIN, 1977) and for operationalization of them, was used the software Atlas Ti 8. The investigation took place in the period of september/2017 to april/2019. The action-research was realized in a city public school in a countryside city of Rio Grande do Sul, performed professional place of the researcher. The involved subjects were ten (10) teachers. In the dissertation are presented the postulations of the work model based in the collaboration between the specialized profesional and the regular class teacher, which envolves an approachment on human rights, in a politics of school inclusion conception which tackles the collaborative work as a possible and fundamental practice in the school environment. We hope with the realization of this research, to help with the reflections about the collaborative teaching work in the perspective of the inclusive education, moving on a sistematic way in the inclusive school process.
Keywords: Atendimento educacional especializado; Trabalho docente colaborativo; Acessibilidade pedagógica; Educação inclusiva; Inclusão escolar; Specialized educational attendance; Collaborative teaching work; Pedagogical accessibility; Inclusive education; School inclusion; CNPQ::CIENCIAS HUMANAS